The Development of Islamic Thought in Historical Perspective - Kamaruddin, Syamsu A (TAWARIKH, 2012)
ABSTRACT: The decline of the Moslem world is caused by the internal factors, followed by the emergence of new problems that come from outside.Â At the beginning of seventeenth century, many Islamic territories â which have already felt the impact of economic and military pressure of Western countries to the Islamic world â gradually shifted from offensive to defensive matters. This paper aims to reveal the development of Islamic thought in historical perspective, with a view refuted the opinion of Western scholars that what the West world today is solely the result of its own product of Renaissance. The thought in Renaissance itself is a product of science and art obtained as a result of imitating the scientific progress generated by Islamic civilization in its heyday. Finally, Moslems should not reject Western modernism as well as postmodernism, but trying to walk side by side to achieve the glory that has been lost. Moslems also need to be ashamed to God for not being able to do the good maximally and do not complete an amazing âsunnatullahâ (natural law created by God) such as actions that are carried out continuously.KEY WORDS: World civilizations, Islamic thought,Â Moslem scholars, Renaissance in the West, and historical perspective.About the Author: Dr. Syamsu A. Kamaruddin is a Senior Lecturer at the Faculty of Education and Teacher Training UVRI (Veteran University of the Republic of Indonesia), Jalan Gunung Bawakaraeng No.72 Makassar, South Sulawesi, Indonesia. He can be reached at: syamsukamaruddin@gmail.comHow to cite this article? Kamaruddin, Syamsu A. (2012). âThe Development of Islamic Thought in Historical Perspectiveâ in TAWARIKH: International Journal for Historical Studies, Vol.3(2) April, pp.177-194. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 25, 2012); Revised (March 29, 2012); and Published (April 28, 2012).